2022
DOI: 10.1186/s12967-022-03280-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the gut microbiome and metabolome profiles of septic rats treated with aminophylline

Abstract: The treatment of sepsis remains a major challenge worldwide. Aminophylline has been shown to have anti-inflammatory effects; however, the role of aminophylline in sepsis, a disease characterized by immune dysregulation, is unknown. In this study, we combined microbiome sequencing and metabolomic assays to investigate the effect of aminophylline administration on the intestinal flora and metabolites in septic rats. Sixty SD rats were randomly divided into three groups: a sham-operated (SC) group, a sepsis model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The Study found that Lactobacillus was the main group of bacteria involved in the 7α-dehydroxylation reaction of cholic acid to DCA [ 22 ]. Lactobacillus showed positive regulation with chenodeoxycholic acid [ 23 ], which was consistent with our experimental results. Futhermore, Lactobacillus possessed bile salt hydrolase (BSH) activity, which promoted the hydrolysis of bile acids in the gut by regulating BSH activity [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…The Study found that Lactobacillus was the main group of bacteria involved in the 7α-dehydroxylation reaction of cholic acid to DCA [ 22 ]. Lactobacillus showed positive regulation with chenodeoxycholic acid [ 23 ], which was consistent with our experimental results. Futhermore, Lactobacillus possessed bile salt hydrolase (BSH) activity, which promoted the hydrolysis of bile acids in the gut by regulating BSH activity [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…This genus has been related to acetic acid production and its influence on lipid metabolism [51]. Lipids regulate biological processes such as immunity and inflammation [52]. In addition, Bacteroides has been associated with the metabolism of bile acids, proteins, fats and carbohydrates [51].…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous studies have found that the abundance of Firmicutes in the sepsis group is reduced. 30,31 Moreover, its abundance increased in the sepsis group after treatment with related drugs. 30,32 The Bacteroidota, also known as Bacteroidetes, is an anaerobic bacterium that plays a role in immunity and 33 It is usually associated with gut inflammation, and its abundance is also different before and after the treatment of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Moreover, its abundance increased in the sepsis group after treatment with related drugs. 30,32 The Bacteroidota, also known as Bacteroidetes, is an anaerobic bacterium that plays a role in immunity and 33 It is usually associated with gut inflammation, and its abundance is also different before and after the treatment of sepsis. 34,35 In the Circos diagram, Firmicutes and Bacteroidota is a dominant species at the phylum level.…”
Section: Discussionmentioning
confidence: 99%